Early and precocious puberty during the COVID-19 pandemic - Prosperi, Sara; Chiarelli, Francesco (Frontiers in Endocrinology, 2023)
During the year 2020, the COVID-19 pandemic rapidly became a severe health emergency worldwide. In order to contrast the spread of the novel SARS-CoV-2, many countries implemented extraordinary restrictive measures, such as a strict lockdown and school closures. The pandemic had a great impact on children and adolescents’ daily life, leading to a much more sedentary lifestyle, to larger use of electronic devices and to an increase in stress-related symptoms. These conspicuous changes acted as disruptors of children’s normal development. Since the beginning of the pandemic, many studies reported an increase in the number of precocious puberty cases as well as a faster progression rate of puberty itself, if compared to the pre-pandemic years. In this review, our aim was to evaluate the incidence of new cases of early and precocious puberty during the COVID-19 pandemic, analyzing variations in the timing of puberty and in pubertal progression rate, and to investigate the role of environmental and lifestyle factors during the pandemic in modulating the physiopathology of pubertal development. While a direct effect of SARS-CoV-2 infection remains, at the moment, a remote hypothesis, both physical and psychological factors related to the pandemic seem to have a role in triggering GnRH pulsatile secretion leading to earlier pubertal onset. It is indeed important to stress the need to clarify the exact role of COVID-19 in early pubertal onset comparing data from all over the world; long-term comprehensive studies are also pivotal to explain whether this phenomenon will continue while we resume pre-pandemic habits.